A descriptive study on selected university students' perception of nationalistic graphic design t-shirts - Neri, Hiyasmin Cherubai M. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT According to Walters (2001), T-shirts have been part of today?s street culture and fashion. They are the simplest and cheapest portable advertisement for visual statements, affiliations and ideas (Walters, 2001). Wearers of T-shirts are able to communicate their interests through designs and statements printed on the shirts, themed to react to situations or to promote important products and events. The Filipino youth fashion has been greatly influenced by several local graphic design companies which promote distinct Filipino influence through affordable and creative graphic T-shirts. Graphics of Filipino icons from different industries such as entertainment, politics, and sports are usually incorporated in shirt designs that appeal to the Filipino consumer. For this reason, a graphic design T-shirt becomes a medium in instilling societal awareness and nationalism to the Filipino youth. This study aimed to determine the perception on nationalistic graphic design T-shirts of university students from University of the Philippines, Diliman, Ateneo de Manila University, and AMA Computer University Q.C. by answering the following questions: (1) What are the nationalistic designs available in the market? (2) Why do the university students wear nationalistic graphic- designed T-shirts? (3) What are the specific preferences of university students in choosing a nationalistic graphic designed T-shirt? (4) Do university students feel nationalistic when wearing nationalistic graphic designed T-shirts? This study was established to: (1)identify available nationalistic graphic designs for T-shirts used in the market as observed by the selected respondents, (2) identify the preferences for and reasons why the selected respondents wear nationalistic graphic designed T-shirts; and (3) determine the respondents? perception on nationalism based on the wearing of nationalistic graphic designed T- shirts. A survey questionnaire was designed by the researcher and was distributed among three Universities, namely- University of the Philippines, Ateneo de Manila University and AMA Computer University. The study randomly selected a total of one hundred fifty (150) respondents; fifty (50) from each university. Frequency distributions, rank orders and charts were used to analyze the data. Results show that most nationalistic graphic designed T-shirts that are available in the market have graphic design variations of Filipino objects, political icons, entertainment icons, sports icons, Philippine maps, Philippine flags and slogans. University students wear nationalistic graphic designed T-shirts because they are trendy and unique. Students wear these shirts because they find it appealing and that they would want to conform to the fashion taste of their peers. Two out of three universities believe that wearing nationalistic graphic designed T-shirts make them feel nationalistic because they promote the country?s culture. However, most students from the University of the Philippines believe that being nationalistic involves action and experience and it is not represented through a fashion statement.